PERBANDINGAN PROGRAM LATIHAN OTAGO MODIFIKASI DAN LATIHAN BERJALAN TERHADAP PHYSICAL PERFORMANCE PADA LANSIA PRE-FRAIL - Vikawati, Nura Eky; Julianti, Hari Peni; Dewi, Novita Sari; Mariani, Endang Sri (RSUP Dr. Kariadi, 2023)
Background: Multicomponent training program like OTAGO is considered to improve the physical performance of pre-frail elderly, thereby reducing risk of fall. The Short Physical Performance Battery (SPPB) is a combination test that assesses physical performance and becomes a fall risk screening test for pre-frail elderly. This study aimed to compare the modified OTAGO to walking training on physical performance as measured by SPPB in the pre-frail elderly. Methods: This was an observational study with a cross-sectional design. The data were taken from the previous study including pre-frail subjects in Prolanis, Gunung Pati area, Semarang before and after giving intervention (modified OTAGO vs walking training) for 6 weeks. The SPPB score was measured from balance function test, chair stand test, and 4-meter walking test before and after the intervention. Data analysis was using SPSS ver 20.0. Paired sample T-test and Wilcoxon signed ranks test were used to analyze the SPPB score before and after interventions in the modified OTAGO and walking training group, respectively. Mann-Whitney U was used to analyze the difference in the average improvement of SPPB score. Results: There was a significant improvement in SPPB score before and after interventions either in modified OTAGO (p=0.013) or walking training (p=0.013). No significant difference was found in the average improvement of SPPB score in both groups (p=0.826). Conclusion: Both modified OTAGO and walking training intervention can improve the physical performance of pre-frail elderly. The modified OTAGO training is not superior in improving physical performance compared to walking training.